Check sibling questions

Misc 3 - f(x) = x2 - 3x + 2, find f(f(x)) - Chapter 1 - Miscellaneous

Introducing your new favourite teacher - Teachoo Black, at only ₹83 per month


Transcript

Misc 3 If f: R → R is defined by f(x) = x2 − 3x + 2, find f(f(x)). f(x) = x2 − 3x + 2. f(f(x)) = f(x)2 − 3f(x) + 2. = (x2 – 3x + 2)2 – 3(x2 – 3x + 2) + 2 = (x2)2 + (3x)2 + 22 – 2x2 (3x) + 2x2(2) – 2x2(3x) – 3(x2 – 3x + 2) + 2 = x4 + 9x2 + 4 – 6x3 – 12x + 4x2 – 3x2 + 9x – 6 + 2 = x4 – 6x3 + 9x2 + 4x2 – 3x2 – 12x + 9x – 6 + 2 + 4 = x4 – 6x3 + 10x2 – 3x Using (a – b + c)2 = a2 + b2 + c2 – 2ab + 2ac – 2ab

Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.